Luminescence of Macrocyclic Mononuclear Dyiii Complexes and Their Immobilization on Functionalized Silicon-Based Surfaces - Aravena-Ponce, D; Aravena-Ponce, D (American Chemical Society, 2022)
Two mononuclear DyIII complexes, [Dy(L1)(NCS)3] (Dy-EDA) and [Dy(L2)(NCS)3] (Dy-DAP), where Ln (n = 1-2) corresponds to a macrocyclic ligand derived from 2,6-pyridinedicarboxaldehyde and ethylenediamine (L1) and 1,3-diaminepropane (L2) were immobilized on functionalized silicon-based surfaces. This was achieved by the microcontact printing (μCP) technique, generating patterns on a functionalized surface via covalent bond formation through the auxiliary -NCS ligands present in the macrocyclic complex species. With this strategy, it was possible to control the position of the immobilized molecules on the surface. Water contact angle measurements, X-ray photoelectron spectroscopy (XPS), infrared reflection absorption spectra (IRRAS), and atomic force microscopy (AFM) confirmed that the surfaces were successfully functionalized. Furthermore, the optical properties in a broad temperature range were investigated for the as-prepared compounds. At room temperature, Dy-EDA was shown to emit in the deep blue region (Commission Internationald Eclairage (CIE): (0.175, 0.128)), while Dy-DAP in the white region (CIE: (0.252, 0.312)). The different CIE values were due to the contribution of the strong emission of the ligand in the case of Dy-EDA. Besides, surface photoluminescence measurements showed that the immobilized complexes retained their bulk emissive properties. © 2022 American Chemical Society.